Low‐Density Lipoprotein Levels are One of the Independent Determinants of Circulating Levels of Advanced Glycation End Products in Nondiabetic Subjects - Yamagishi, Sho‐ichi (Clin Cardiol, 2009)
BACKGROUND: Nonenzymatic modification of proteins by reducing sugars leads to the formation of advanced glycation end products (AGEs), whose process has been reported to progress under diabetes. Recently, diet has been found to be a major environmental source of proinflammatory AGEs in humans. Further, fats or meat‐derived products processed by high heat such as broiling have been shown to contain more AGEs than carbohydrates boiled for longer periods. Since circulating levels of low‐density lipoprotein cholesterol (LDL‐C) are also regulated by dietary cholesterol, it is conceivable that intake of cholesterol‐rich foods could regulate serum levels of AGEs in humans. In this study, we investigated whether LDL‐C levels are one of the independent determinants of circulating AGEs levels in a nondiabetic general population. METHODS: A total of 170 nondiabetic Japanese subjects underwent a complete history, physical examination, determination of blood chemistries, and serum AGEs. RESULTS: Univariate analysis showed that AGEs levels were associated with LDL‐C (P < 0.05) and fasting plasma glucose levels (P < 0.05). By the use of multiple stepwise regression analyses, LDL‐C (P < 0.01) and fasting plasma glucose levels (P < 0.05) remained significant and were independently related to AGEs levels (R (2) = 0.069). CONCLUSIONS: The present study is the first demonstration that LDL‐C levels are one of the independent determinants of serum levels of AGEs in a nondiabetic general population. Intake of cholesterol‐rich foods may regulate serum levels of AGEs in nondiabetic subjects. Copyright © 2009 Wiley Periodicals, Inc.